The impact of the cube strategy on mindfulness and learning the skills of setting and receiving serves in volleyball for students - Qader, L.Dr. Abbas Majeed (Sulaimani Journal for Humanities, 2026)
The purpose of this research was to identify the effect of the cube strategy on mental alertness and the performance of two skills (setting and receiving serves) among second-year volleyball students. The researcher adopted the experimental method and its hypotheses, employing a two-group design with two equivalent groups: an experimental group and a control group, using pre-tests and post-tests. The research population consisted of second-year students at the College of Physical Education and Sports Sciences, University of Kirkuk, during the academic year 2023/2024, totaling 80 students. Ten students were selected for a pilot study and subsequently excluded from the sample. Six additional students were excluded due to absenteeism, resulting in a research sample of 64 students distributed across two sections (A and B). The research sample was randomly selected by lottery, with section (A) designated as the experimental group and section (B) as the control group, resulting in a total of 32 students in each section (A and B). The research sample was then randomly selected by lottery. By presenting, analyzing, and discussing the results for both the experimental and control groups, the researcher reached the following conclusions in Chapter Four: 1- The cube strategy, using diverse learning units, positively impacted the mindfulness and performance of the two skills (setting and receiving serves) of second-year volleyball students, surpassing the group that used the standard method. 2- The use of the cube strategy effectively enabled the students in the experimental group to better understand mindfulness
Keywords: Cube strategy; mindfulness; setting skills; receiving and serving skills; volleyball